PEREMPUAN DALAM AL-QUR’AN DAN GERAKAN ORGANISASI MASYARAKAT ISLAM ANTI KESETARAAN - Zuhdi, M Nurdin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
Start from the decline in awareness of Muslims because of imperialism and Western hegemony makes Muslims started to straighten ourselves out of recession. Since then buzzed the glory of the Islamic revival. Even at the point of life is the rise of Islam has become an international phenomenon. Awakening consciousness departs from the central theme: fight and beat back attacks from internal crash parties to discredit the foreign Muslims. This movement logosentrisme Islamic Estuary. It is believed as a shortcut only to get out of the crisis and degradation, with the triumph of Islam aspired. Revival movement is trying to grow back the spirit of faith, the stagnation of thought and jurisprudence, as well as movement (harakah) and jihad. This also brings resurrection exam for Muslims so that encourages them to find the causes of falls and the opprobrium that hit. Moving on from this consciousness, they find a new awareness, namely: changing the faith, activate thoughts, and stimulate the Islamic movements. In ndonesia itself has grown and developed a kind of revival movement is a movement, example as Ikhwanul Muslim, Hizbut Tahrir, the Salafi Movement etc. They apparently had a big hand in developing the movement to promote Islamic revivalism in Indonesia.